(untitled) (Research, Society and Development, 2023)
The effect of phosphate fertilization (0, 30, 60 and 120 kg of P2O5 ha-1) on forage production and morphogenetic and structural characteristics of Axonopus aureus was evaluated under natural field conditions in the savannas of Roraima. Phosphate fertilization positively and significantly (P<0.05) affected green dry matter (GDM) production, absolute growth rate (AGR), number of tillers plant-1, number of leaves tiller-1 (NLT), average leaf size (ALS), leaf tiller area (LTA), appearance rates (LAR), expansion (LER) and leaf senescence rates. The maximum yields of GDM, AGR, LAR, LER, NLT, LTA and ALS were obtained with the application of 110.4; 108.5; 54.1; 83.5; 96.6; 59.8 and 90.6 kg of P2O5 ha-1, respectively. The efficiency of P utilization was inversely proportional to the P doses applied.